Resilient Coping Types in People With Spinal Cord Injury: Latent Class Analysis. (April 2022) - Chiu, Chungyi; Brooks, Jessica; Jones, Alicia; Wilcher, Kortney; Shen, Sa; Driver, Simon; Krause, James
Resilience is central to living well with a spinal cord injury (SCI). To provide a timely, targeted, and individualized intervention supporting resilience, it is necessary to assess an individual's resilience level and characteristics of resilience on an ongoing basis. We aimed to validate the different types of resilient coping among people with SCI (PwSCI), using the Connor–Davidson resilience scale, and to identify the relationships between resilience and other psychosocial factors among the types of resilient coping. We recruited 93 PwSCI, who took the self-report measures of resilience, depression, life satisfaction, and spirituality. Using latent class analysis, we found three types: (a) goal-pursuing, bouncing-back, and persevering, named GP; (b) uncertainty about coping with setbacks, named UC; and (c) loss of resilient coping, named LOSS. The multivariate tests indicated that the three types differed on a linear combination of resilience, depression, and life satisfaction, with a large effect size. We discuss the three types of resilient coping and the implications for psychosocial interventions. We also recommend that rehabilitation clinicians examine PwSCI's resilience levels and types of resilience during initial and follow-up visits. In doing so, PwSCI will have timely, targeted supports for developing and/or re-building their resilience.